Creating A Healthy Lifestyle of Students Through the Use of The SEKA Application (Health Campus) - Aryani , Enggar Wahyu Putri; Ramadhan, Persistent; Wiranatakusuma, Dimas Bagus (Universitas Muhammadiyah Yogyakarta, 2023)
In this modern era, a healthy lifestyle has become a major concern for many people, including students. College students often face high academic pressure and social demands, which can have a negative impact on their health. Therefore, it is important for students to maintain their physical and mental health so that they can optimally achieve their academic and personal potential. A healthy lifestyle is becoming increasingly important in everyday life, especially for students who often face academic pressures and lack a lifestyle. Healthy. To help students maintain their health, we propose to make an application called